PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN PENGGUNA JASA TRANSPORTASI UMUM TRANS BATAM - SISKA ANDRIANI SIANIPAR; HENDRI HERMAN (JURNAL ILMIAH KOHESI, 2020)
This study aims to understand or find out whether there is an influence on the quality of services and facilities on thesatisfaction of users of Trans Batam public transportation services. And to measure and test the hypotheses in this studythrough quantitative descriptive methods. The population of this study is the user who uses Trans Batam buses, thepopulation is not limited, therefore the sample used uses the Issac and Michael table formula which amounts to 272 people.In order for this study to obtain data, conducted through observation, questionnaires. The data analysis technique used indata processing in this study is the Likert scale and uses 25. Based on the result of the t test results show that the t-tablevalue of Service Quality variable 5.769 > t-table 1.651 and the significance value is 0.000 < 0.05. and facilities 8.701 > t-table1.651 and a significant value of 0.000 < therefore the researcher knows that there is a positive and significant influencebetween the quality of services and facilities on user decisions, and compared with the quality of service and facilitiessignificantly affect user satisfaction.